ANALISA KESENJANGAN (GAP) PRODUKTIVITAS TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TIGA TAHUN TANAM DI AFDELING V KEBUN LAMA PT. PERKEBUNAN NUSANTARA I - Rina Maharany; Sri Murti Tarigan; Saddam Al Ghazali (Universitas Asahan, 2019)
The productivity of oil palm fruit bunches increases rapidly and reaches a maximum at the age of 8-12 years, then decreases slowly with plants getting older to 25 years of economic age. This research was conducted in Afdeling V Kebun Lama PT. Perkebunan Nusantara I. This research was conducted in May until July 2018. This research was using descriptive analysis, by using oil palm productivity data in Afdeling V Kebun Lama PT. Perkebunan Nusantara I. The results showed that the average number of bunches per tree in 2015-2017 was 7.59% lower than the potential, the average bunch weight was 32.06% lower than the potential, and the average productivity of FFB was lower 37.47 % of potential. The gap in oil palm productivity in Afdeling V Kebun Lama PTPN I was influenced by several factors, namely rainfall factors, plant age factors, fertilization factors, number of tree stands per hectare (SPH), and plant disease factors.